Effects of cereal rye residue biomass and preemergence herbicide on the emergence of troublesome southeastern weed species - Kumari, Annu; Price, Andrew J.; Li, Steve; Gamble, Audrey; Jacobson, Alana (Frontiers in Agronomy, 2025)
Cover crops are increasingly adopted to suppress weed growth and reduce reliance on chemical herbicides. A greenhouse experiment was conducted to evaluate the emergence and growth response of troublesome southeastern weeds to various cereal rye (Secale cereale L.) residue levels. Trays planted with Palmer amaranth (Amaranthus palmeri S. Watson), sicklepod (Senna obtusifolia L.), ivyleaf morningglory (Ipomoea hederacea), and large crabgrass (Digitaria sanguinalis L.) seeds mixed with soil were covered uniformly by four different levels of cereal rye biomass. The following field experiment was conducted at two locations in Alabama in a split-plot design, with the main plot factor being four seeding rates of cereal rye to obtain various cereal rye biomass. Subplot factors were preemergence herbicide flumioxazin and non-treated (NT) check. The greenhouse results demonstrated reduced seed emergence and lower weed biomass for Palmer amaranth, sicklepod, and large crabgrass in plots with higher cereal rye residue biomass compared to those with lower biomass. In both greenhouse and field conditions, the emergence of ivyleaf morningglory was not affected by the increasing biomass of cereal rye residue. Palmer amaranth seed emergence was the most sensitive to increasing biomass residue due to its small seed size. Cereal rye biomass and Palmer amaranth counts were strongly negatively correlated with a Pearson’s coefficient (r) of 0.83 while weakly negatively correlated for ivyleaf morningglory with 0.49. In conclusion, increasing the biomass of cereal rye residue is effective in suppressing Palmer amaranth seed emergence but not ivyleaf morningglory. The flumioxazin treatment demonstrated 95%–90% control for Palmer amaranth and ivyleaf morningglory, while the NT check exhibited 50% control of Palmer amaranth and 30% control of ivyleaf morningglory by cereal rye biomass alone. In conclusion, a sufficient amount of cereal rye biomass can effectively suppress the emergence and growth of weeds, particularly Palmer amaranth.